Effects of post-veraison irrigation regime on Cabernet Sauvignon grapevines in Valencia, Spain: Yield and grape composition - Intrigliolo, Diego S.; Lizama, V.; García-Esparza, María J.; Abrisqueta, I.; Álvarez, Inmaculada (Elsevier, 2020)
tIn the old-world viticulture, there is a common but most often not scientifically proven considerationthat supplemental irrigation should detrimentally affect berry and wine composition. In the temperate-warm climate of inland Valencia (Spain), during three growing seasons (2009–2011), the effects of post-veraison deficit irrigation regime on Cabernet Sauvignon vine performance and berry composition weredetermined. Rainfed vines were compared with three post-veraison deficit irrigation regimes replacing25, 50 and 75% of the estimated crop evapotranspiration, resulting in water application of 37, 67 and128 mm, respectively. Rainfed vines experienced quite severe plant water stress, reaching, in two outof the three experimental seasons, midday stem water potential values as low as −1.6 MPa. Despitethis, rainfed vines at harvest had the highest concentration of berry total soluble solids and phenolicsamong all tested water regimes. This was most likely a consequence of berry dehydration which, in therainfed vines, resulted in a reduction of berry size, while in the irrigated treatments a constant increase infresh berry weight was observed during the ripening period. As a consequence, the two greater irrigatedtreatments resulted in a 26–30% yield increase. In addition, when replacing half of the potential waterneeds, total water use efficiency could be maintained at similar levels as in rainfed vines. In any case,the main positive effect of the supplemental irrigation application was to avoid the excessive increasein berry sugar content, which at commercial vintage time reached up to 16.5% of probable alcohol inthe rainfed treatment. It is therefore concluded that moderate post-veraison irrigation water applicationmight result in a more balanced sugars-phenolics grape composition while considerably increasing yieldin comparison with the rainfed regime. In any case, the most convenient irrigation strategy might dependon the desired grape style and, indeed, on wine consumer preferences